Hubungan Perilaku Caring Perawat Terhadap Tingkat Kepuasan Pasien Di Ruang Rawat Inap Rumah Sakit Lavalette Malang - Pudjiastutik, Erliana; Febriani , Reny Tri; Kurniawan, Andi Surya; Trigantara, Regista (Jurnal Keperawatan Muhammadiyah, 2025)
Caring is a central professional nursing practice that provides a positive contribution to patient satisfaction to improve the quality of nursing services in a hospital. This study aims to determine the relationship between caring behavior of inpatient nurses and the level of satisfaction of inpatients at Lavalette Hospital, Malang. The research design used in this study was observational analytic with a cross-sectional study approach with a sample size of 80 respondents with non-probability sampling through a purposive sampling approach. Data analysis used to analyze the relationship between caring nurses and the level of satisfaction using Spearman's rho analysis where both variables are ordinal. The test results showed that most nurses had provided good caring and patients were also very satisfied with the services provided (72.5%). From the test results, ρ = 0.000 was obtained, meaning ρ <0.05, this shows a significant relationship between caring nurses and the level of patient satisfaction in the inpatient room of Lavalette Hospital, Malang City. The application of caring behavior for a nurse can affect the level of patient satisfaction. So the higher the caring nurse, the higher the level of patient satisfaction